Pengaruh Pembinaan Dan Kompentensi Terhadap Kinerja Karyawan (Studi Pada PT Nindya Karya (Persero) Bagian Cabang Mataram) - Sayyidatul Mu’minah; Thatok Ismony; Djoko Suprayetno (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
In order to achieve company goals, it is necessary to improve employee performance, the company must be able to utilize human resources optimally. This study examines the effect of coaching and competence on employee performance at PT. Nindya Karya Mataram Branch. The data collection method used is a census method by using primary data collected directly from respondents through filling out questionnaires. The type of research used is quantitative research with an associative approach. The number of respondents in this study was 40 respondents. The analysis tool used is Multiple Linear Regression analysis using SPSS program version 25.0. The results of the analysis show that: (1) the coaching variable has a significant and positive effect on the performance of PT. Nindya Karya Mataram Branch; (2) competence variables have a significant and positive effect on the performance of PT. Nindya Karya Mataram Branch.